Corruption issues in China: an interview with Jianyuan Yang - Senz, Anja-Désirée (Bribery, fraud, cheating, 2020)
Anja Senz: Dear Ms. Yang, thank you for your willingness to speak with us and to answer the following questions. To start with, could you please give us some brief background information about Fangda Partners, a leading law firm in China, and your responsibilities there?